Effect of recombinant interleukin 2 on hepatitis B e antigen positive chronic hepatitis. - Onji, M (1987)
Eleven patients with hepatitis B (HB) virus related chronic hepatitis were treated with recombinant interleukin 2 (rIL 2). Two hundred and fifty to 1000 units were given intravenously once daily for seven to 28 days. In five patients serum glutamic pyruvic transaminase activity rose transiently. Six patients showed a decrease in HBV DNA polymerase. One patient lost HBs, e antigens (Ags) and gained anti-HBs, e antibodies, while one lost HBs Ag and another HBe Ag. 2'-5' oligoadenylate synthetase activity in mononuclear cells in the peripheral blood did not change during treatment. The number of CD4 positive (helper/inducer) cells and natural killer cell activity increased after therapy (p less than 0.05, p less than 0.01). These results suggest that rIL 2 acts as an immunomodulatory agent enhancing host immune activity and may be beneficial in patients with chronic HB virus infection.